In vivo evaluation of angulated needle‐guide template for MRI‐guided transperineal prostate biopsy. Issue 5 (24th March 2021) - Moreira, Pedro; Grimble, John; Iftimia, Nicusor; Bay, Camden P; Tuncali, Kemal; Park, Jesung; Tokuda, Junichi
Abstract : Purpose: Magnetic resonance imaging (MRI)‐guided transperineal prostate biopsy has been practiced since the early 2000s. The technique often suffers from targeting error due to deviation of the needle as a result of physical interaction between the needle and inhomogeneous tissues. Existing needle guide devices, such as a grid template, do not allow choosing an alternative insertion path to mitigate the deviation because of their limited degree‐of‐freedom (DoF). This study evaluates how an angulated needle insertion path can reduce needle deviation and improve needle placement accuracy. Methods: We extended a robotic needle‐guidance device (Smart Template) for in‐bore MRI‐guided transperineal prostate biopsy. The new Smart Template has a 4‐DoF needle‐guiding mechanism allowing a translational range of motion of 65 and 58 mm along the vertical and horizontal axis, and a needle rotational motion around the vertical and horizontal axis ± 30 ∘ and a vertical rotational range of ‐ 30 ∘, + 10 ∘, respectively. We defined a path planning strategy, which chooses between straight and angulated insertion paths depending on the anatomical structures on the potential insertion path. We performed (a) a set of experiments to evaluate the device positioning accuracy outside the MR‐bore, and (b) an in vivo experiment to evaluate the improvement of targeting accuracy combining straight and angulated insertions in animal models (swine, n = 3 ). Results: We analyzed 46 in vivo insertions using either straight or angulated insertions paths. The experiment showed that the proposed strategy of selecting straight or angulated insertions based on the subject's anatomy outperformed the conventional approach of just straight insertions in terms of targeting accuracy (2.4 mm [1.3–3.7] vs 3.9 mm [2.4–5.0] Median IQR ); p = 0.041 after the bias correction). Conclusion: The in vivo experiment successfully demonstrated that an angulated needle insertion path could improve needle placement accuracy with a path planning strategy that takes account of the subject‐specific anatomical structures.